Achieving an excellent thermoelectric performance in nanostructured copper sulfide bulk via a fast doping strategy. (March 2019) - Ge, Z.-H.; Chong, X.; Feng, D.; Zhang, Y.-X.; Qiu, Y.; Xie, L.; Guan, P.-W.; Feng, J.; He, J.
Abstract: Although the Cu1.8 S compound consisting of cheap and earth-abundant elements has been reported to be a potential candidate of thermoelectric material, its thermoelectric performance is not very high. In this work, a fast doping strategy is offered to introduce both point defects and nanostructures into thermoelectric materials to improve the performance. Ball-milled Cu1.8 S powders were mixed with different amounts of In2 S3 powders and were then sintered into bulk samples by the spark plasma sintering (SPS) technique. During the SPS process, In2 S3 was doped into the Cu1.8 S matrix at 723 K for 10 min, and the fast doping process results in point defects and nanostructures of the Cu1.8 S bulk sample including nanopores and those with an included second phase. On the one hand, In doping increased the effective mass of charge carriers in Cu1.8 S and improved the Seebeck coefficient, whereas on the other hand, the nanostructures reduced thermal conductivity significantly. The phase structure and microstructure of Cu1.8 S bulks are highly dependent on the In2 S3 content. Density functional theory calculations revealed that Cu1.8 S has an intrinsically low lattice thermal conductivity because of low-frequency localized vibrations from the Cu ionic migration and Cu vacancies. As a result, Cu1.8 S+3  wt % In2 S3 bulk sample achieved a ZT value of ∼1.4 at 773 K compared with that of 0.45 at 773 K for the pristine Cu1.8 S sample; this value is the highest ZT value in sulfide thermoelectric materials at this temperature. The fast doping strategy demonstrated in this work can also be applied for reducing thermal conductivity and improving ZT values of other thermoelectric systems. Graphical abstract: Image 1 Highlights: The nanostructured Cu1.8 S bulk sample with excellent thermoelectric properties was obtained by a fast doping strategy. The nanostructure of nanopores with an inside second phase was observed. The formation mechanism of the nanostructure was discussed in detail. The nanostructures contribute to a high ZT value of 1.4 at 773 K for the Cu1.8 S bulk sample, which is the highest ZT value for sulfides.